PENGARUH DIKLAT, MOTIVASI DAN KREATIVITAS TERHADAP KINERJA KARYAWAN PT. LEBAH SEMESTA - Adhika, I Nyoman Resa (Jurnal Manajemen, 2022)
Employee performance really needs to be done to improve company performance. The purpose of this study was to determine the effect of training, motivation and creativity on the performance of PT. Lebah Semesta employees. The population and samples taken were 43 respondents, with the sampling method using a saturated sample or census. The analysis technique used is multiple linear regression. The results showed that the education and training had a positive and significant effect on the performance of the employees of PT. Lebah Semesta. Motivation has a positive and significant effect on the performance of PT. Lebah Semesta employees. Creativity has a positive and significant effect on the performance of PT Lebah Semesta's employees.